Coaching Sprinting: Expert coaches' perception of race phases and technical constructs - Jones, R.; Bezodis, I.; Thompson, A. (International Journal of Sports Science and Coaching, 2009)
The general aim of this study was explore expert coaches' technical knowledge of sprint running. The first of two principal objectives related to discovering whether expert coaches divided a sprint race into distinct phases and, if so, which and how many phases. The second objective was to examine the good technique characteristics associated with each phase. Participants for the study comprised seven expert track and field sprint coaches. Findings indicated that the respondents broke sprinting down into three technical phases, the start, the pick-up/drive and the maintenance phase. Important constructs were associated with each phase, which both supported and conflicted with the limited literature available. The principal finding of this study, however, relates to the current dearth of knowledge about good sprint-running technique, an area which requires considerable further investigation before definitive lines of good practice can be confidently applied.